Low cycle fatigue analysis of marine structures - Tan, Jeremy Wei Ming. (2012)
Fatigue failure is a result of a repeated application of dynamic and fluctuating stresses which is of a lower intensity than those that would cause failure on a single application. Much research has been done on fatigue analysis for high cycle fatigue failure which accounts for failure that occurs for loading cycles of more than 10^4, however, low cycle fatigue failure for marine structures had only been recognized in recent years due to the discovery of cracks in ships within a few years of delivery.